Fabrikasi Model Anatomi 3-D menggunakan 3-D Printing untuk Simulasi Proses Operasi Total Knee Replacement (TKR) berdasarkan Rekonstruksi Pemindaian CT/MRI sebagai Alat Edukasi dan Pelatihan - Irfan Aditya Dharma; Muhammad Fernanda Darmawan (Mechanical Engineering Department - Semarang State Polytechnic, 2023)
Currently, 3-D printing or additive manufacturing technology has been widely used to fabricate anatomical 3-D models of human body parts based on CT/MRI Scan reconstructions. Anatomical 3-D models resulting from 3-D printing have many applications, such as educational tools, specific implants, concepts of preoperative planning, etc. This research focuses on the reconstruction of the knee bones, modeling the Total Knee Replacement (TKR) prosthetic knee joint, and creating a 3-D anatomical model for TKR surgery simulation model using a fused deposition modeling (FDM) 3D print type. The results of the 3-D anatomical model using a 3D print can demonstrate a simulation of the TKR operation and installation according to the operating procedure with the limitation of the surgical process only to cutting the bone and inserting a prosthetic knee joint.